PEMBUATAN MODEL PENDETEKSI API BERBASIS ARDUINO UNO DENGAN KELUARAN SMS GATEWAY - Dendy Handy Saputra; Nida Nabilah; Hannif Izzatul Islam; Gagat Mughni Pradipta; Sofyan Said Atsaurri; Ade Kurniawan; Heriyanto Safutra; Ardian Arif; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
We has been successfuly to create a model fire detection based arduino uno with the output SMS Gateway. This tool assisted using two sensors are MQ-2 sensor and Fire sensors infrared. In this experiment conducted research on flame sensor infrared sensitivity by using tool such as Lux Meter to measure light intensity at the source of the fire. This research using distance to determine the sensitivity Lux Meter and the fire sensor. This distance used starting from 10 cm up to 110 cm with a 10 cm difference and the fire source used is 2 pieces of wax. In the first experiment using Lux Meter, the result obtained are at a distance of 10 cm the amount of light intensity of 132 lux but if the distance is farther the magnitude of the intensity of light getting down, llike a distance of 100 cm and 110 cm then the magnitude just 0 lux. In the second experiment using Flame sensor, the result obtained are at an angle of 00 with a distance 10 cm up to 90 cm this sensor can detect the fire, but at a distance 100 cm and 110 cm the sensor can’t detect the the fire. While at an angle of 300 to 600 sensors can only detect at a distance 10 cm. Keywords: arduino uno, flame sensor, lux meter, sensor mq-2, sms gateway.